Influence of live and dead earthworms on carbon stabilization and sequestration through mineral weathering - Calogiuri, Tullia; Hagens, Mathilde; van Groenigen, Jan Willem; Wichern, Florian; Poetra, Reinaldy P; Rieder, Lukas; Janssens, Ivan A; Hartmann, Jens; Neubeck, Anna; Niron, Harun; Singh, Abhijeet; Vlaeminck, Siegfried E; et al. (PANGAEA, 2025)
The dataset consists of a list of treatments and relative analyses done to determine different pathways through which live and dead earthworms can influence organic carbon stabilisation and inorganic carbon sequestration through mineral weathering. Data was obtained from a column-experiment of the duration of 120 days, with a mid-term sampling at 60 days to observe changes over time, done between October 2023 and February 2024. The column-experiment was carried out in an incubator at 20 °C, where columns where filled with a mixture of rock powder and 13C labelled plant residues, and earthworms were introduced either alive or dead. The data is separated into two datasets. The first dataset relates to the list of treatments and parameters measured to determine the effect of earthworms, either alive or dead, on carbon dynamics measured at 60 and 120 days. These include measurements such as 13C analyzed in dissolved inorganic carbon, mineral associated organic carbon, microbial analyses, and a series of weathering indicators, as alkalinity and major cations. The second dataset includes measurements on carbon dioxide emissions measured over the whole duration of the experiment for the different treatments. Data was collected within the BAM! project (Bio-Accelerated Mineral Weathering), examining the potential of soil organisms to enhance mineral weathering for carbon sequestration.
Keywords: carbon sequestration; Carbon stabilization; Dead earthworms; Live earthworms; mineral weathering